Team decision-making: the integration of cognitive task analysis and video to accelerate the development of tactical shared mental models in an elite sports team - Richards, Pamela; Robbins, Mandy; Collins, Dave (Frontiers in Sports and Active Living, 2025)
IntroductionThe focus of this article is on developing and operationalising shared mental models in elite sports teams, using a Decision-Making Framework.The Decision-making Framework innovatively integrates Cognitive Task Analysis (CTA) methods into off-field after action review meetings (AAR) to enhance on-field performance.MethodsUsing a mixed method approach, fourteen international players and three expert coaches participated in this study. CTA methods were employed during a 31 day training period, to capture development in individual and team decision-making.ResultsBoth qualitative statements and inferential statistics indicate that DM can be accelerated when a slow, deliberate, reflective, off-field digital environment (AAR) is integrated with competitive ‘in-action’, on-field contexts.ConclusionThe DM Framework accelerated and enhanced individual and team decision-making.